Transforming museum management evidence-based change through open systems theory - Jung, Yuha (Routledge research in the creative and cultural industries, 2022)
Museums must change to illuminate the histories, cultures, and social issues that matter to their local population. Based on a unique longitudinal ethnographic study, Transforming Museum Management illustrates how a traditional art museum attempted to transform into a more inclusive and community-based institution. Using open systems theory and the Buddhist concept of mutual causality, it examines the museum's internal management structure and culture, programs and exhibitions, and mental models of museum workers. In providing both theoretical and practical foundations to transform management structures, this accessible volume will benefit stakeholders by proposing a new culture and structure to arts institutions, to change practice to be more relevant, diverse, and inclusive. This book will be an invaluable resource for researchers and advanced students of museum studies, cultural management, arts administration, non-profit management, and organizational studies"--Provided by publisher.